The association between acid–base status and clinical outcome in critically ill COVID-19 patients admitted to intensive care unit with an emphasis on high anion gap metabolic acidosis. (March 2023) - Zemlin, Annalise E; Sigwadhi, Lovemore N; Wiese, Owen J; Jalavu, Thumeka P; Chapanduka, Zivanai C; Allwood, Brian W; Tamuzi, Jacques L; Koegelenberg, Coenraad F; Irusen, Elvis M; Lalla, Usha; Ngah, Veranyuy D; Yalew, Anteneh; et al.
Objective: The aim of this study was to identify arterial blood gas (ABG) abnormalities, with a focus on a high anion gap (AG) metabolic acidosis and evaluate outcomes in coronavirus disease 2019 (COVID-19) patients admitted to the ICU. Methods: A retrospective, observational study was conducted in a tertiary hospital in Cape Town during the first and second COVID-19 waves. Age, gender, sodium (Na), potassium (K), chloride (Cl), bicarbonate (HCO3 std), pH, partial pressure of carbon dioxide (pCO2 ), creatinine, estimated glomerular filtration rate (eGFR), lactate levels and ABG results were obtained. The Pearson χ2 test or Fisher exact test and the Wilcoxon rank-sum test were used to compare mortality and survival. To identify factors associated with non-survival, a multivariable model was developed. Results: This study included 465 patients, 226 (48%) of whom were female. The sample population's median (IQR) age was 54.2 (46.1–61.3) years, and 63% of the patients died. ABG analyses found that 283 (61%) of the 465 patients had alkalosis (pH ≥ 7.45), 65 (14%) had acidosis (pH ≤ 7.35) and 117 (25%) had normal pH (7.35–7.45). In the group with alkalosis, 199 (70.3%) had a metabolic alkalosis and in the group with acidosis, 42 (64%) had a metabolic acidosis with an increased AG of more than 17. Non-survivors were older than survivors (56.4 years versus 50.3 years, p < .001). Conclusion: Most of the COVID-19 patients admitted to the ICU had an alkalosis, and those with acidosis had a much worse prognosis. Higher AG metabolic acidosis was not associated with patients' characteristics.